Intracellular FMRpolyG-Hsp70 complex in fibroblast cells from a patient affected by fragile X tremor ataxia syndrome. Issue 6 (June 2019) - Bonapace, Giuseppe; Gullace, Rosa; Concolino, Daniela; Iannello, Grazia; Procopio, Radha; Gagliardi, Monica; Arabia, Gennarina; Barbagallo, Gaetano; Lupo, Angela; Manfredini, Lucia Ilaria; Annesi, Grazia; Quattrone, Aldo
Abstract: Background: Fragile X-associated tremor/ataxia syndrome is a late-onset neurodegenerative disorder that affects about 40% of carriers of CGG-repeat expansions in the premutation range within the fragile X gene ( FMR1 ). Main clinical features include intention tremor, cerebellar ataxia, and parkinsonism. Recently, great emphasis on the deposition of soluble aggregates produced by a RAN translation process, as main pathogenic mechanism, has been given. These aggregates contain a small protein with a polyglycine stretch on the aminoterminal end named FMRpolyG and, so far, have been isolated and characterized in drosophila and mouse models, in post mortem brain of fragile X-associated tremor/ataxia syndrome patients, in fibroblasts of fragile primary ovarian insufficiency patients, but never in fibroblasts from a fragile X-associated tremor/ataxia living patients. In adult carriers the syndrome is frequently misdiagnosed due to the lack of specific markers. Methods: We standardized immunocytochemistry, immunoprecipitation and western blot procedures to study and biochemically characterize the FMRpolyG protein in fibroblasts from human skin biopsy. Results: We demonstrate for the first time, in fibroblasts from a patient affected by Fragile X-associated tremor/ataxia syndrome, the presence ex vivo of inclusions consisting of FMRpolyG- Hsp70 soluble aggregates. Conclusion: These observations can pave the way to develop a cellular model for studying ex vivo and in vitro the mechanisms involved in the production of FMRpolyG aggregates, their toxicity, and the role of the FMRpolyG-Hsp70 interaction in the pathogenesis of fragile X-associated tremor/ataxia syndrome.